Evaluating the impact of sandblasting and spray coating on surface thickness in ABS 3D printed parts - Haidiezul, A.H.M.; Dolah, M.S.; Khalid, M.; Shuaib, N.A.; Omar, N.A.; Mahmud, A. (Universiti Teknikal Malaysia Melaka, 2024)
In Fused Filament Fabrication (FFF) 3D printing, surface irregularities and roughness, often referred to as the "stair-stepping" effect, reduce part quality in terms of mechanical performance and visual appeal. Conversely, post-processing techniques can improve the surface finish, but their influence on the surface thickness is still not clear. It is related to the fact that this lack of knowledge impairs the optimization of these methods for increased quality of the surface of the part without impairing the dimensional accuracy. This study aims to investigate and compare the impacts of sandblasting and spray coating post processing methods on the surface thickness of ABS FFF 3D printed parts to improve surface quality. The sandblasting process and spray coating process were used to analyses the influence of both technique to the surface thickness of ABS printed parts. The result of sandblasting shows 1.64 µm of thickness when using with 106 µm of aluminum oxide abrasive size. The thickness reduced to 0.93µm with 29.5 µm of abrasive size. Then, spray coating provided higher surface thickness 6.79µm when using 100 kPa of pressure with three-layer of coating. The sample shows 8.55µm of surface thickness when the pressure was increased to 800 kPa with one-layer of coating. Therefore, this paper provides scientific knowledge and solutions to improve surface quality by focusing at surface thickness of ABS 3D printed parts.